(untitled) (Journal of Basic and Applied Research in Biomedicine, 2022)
Silver nanoparticles, among others, have broad-spectrum antimicrobial properties. Silver nanoparticles have suppressed dangerous microorganisms in medical and agricultural settings in several studies. Chemicals are harmful to humans and the environment, raising awareness of bioactive synthetic methods. These methods produce nanoparticles with better physicochemical qualities, stability, and toxicity. Biogenic nanoparticles can be made from bacterial and fungal byproducts that reduce and stabilize. Encapsulating these nanoparticles with biomolecules from the producing organisms may boost stability and biological activity. Nanoparticles’ quick, clean, cheap, and ecological biologic manufacturing technique increases biocompatibility. Silver nanoparticles affect fish, algae, cell-based in vitro procedures, and microbes. Even though most of these studies were done quickly in well-regulated labs with much higher silver ion concentrations than in real life. Many silver types undergo long-term chemical transformation at extremely low levels (ng/L to g/L) in aquatic ecosystems. Thus, silver nanoparticles’ environmental and health hazards need additional investigation. Recently detected antimicrobial silver at 10102 μg/mL. Multiple processes make silver nanoparticles dangerous. Basic (Ag0) and monovalent (Ag+) silver are most poisonous. Silver framework free ions affect silver toxicity. ROS damage DNA when elemental or zero-valent silver penetrates tissues. Packaged foods, contaminated water, swimming pools, antifouling, nasal and throat medicines, and other pharmaceuticals include silver nanoparticles. Consumption accumulates silver ions in subcutaneous fat. Prolonged exposure causes argyria-blue-gray skin. Silver inhibits Na+ and Cl absorption, disrupting electrolytes. Airborne silver nanoparticles may influence chronic pulmonary disease patients. Silver ions oxidize enzyme thiols, hindering electron transport and DNA replication. Ag+ rapidly damages DNA and RNA. Silver nanoparticle breakdown into silver ions creates germ-killing ROS. Silver nanoparticles are more hazardous than silver ions in the same atmosphere.